Hair-trichomes-files, and spectrochemistry of Macroneuropteris scheuchzeri (Basal Cantabrian, Sydney Coalfield, Canada) - Zodrow, Erwin L. (2014)
Hoffmann's species Neuropteris Scheuchzeri in Keferstein 1827 is generally but not exclusively identified by its 1-4 mm long trichomes or hairs, though he did not mention nor illustrate them in the diagnosis of the species.  Basal Cantabrian-age compressions of the species, including 'Odontopteris subcuneata', from Sydney Coalfield, Canada, are oxidized/macerated by Schulze's process from 3 hours to 12 days to track solubility patterns of the trichomes or hairs, and files. Proposed is also a spectrochemical model for Macroneuropteris (ex Neuropteris) scheuchzeri based on carbon 13 nuclear magnetic resonance (13C NMR) experiments, combined with Fourier transform infrared (FTIR) spectroscopy. M. scheuchzeri is chemically similar to other medullosaleans in respect to high aliphatic and low aromatic contents, though FTIR analysis signals preservation variability. Hair invariably drops from compressions during HF treatment, it is opaque, pointed and not organically attached to compressions. A secretory origin is hypothesized that requires confirmation, including explanation of physiological function. Files-hair-trichomes, besides dissolving at different rates when oxidized, are physicomorphologically distinguishable from one another; hence hair and trichomes are not synonymous, as assumed by some authors.Morphological/functional-group changes occur across the basal frond dichotomy (bfd). Apart from the 'pinnule' differences is that above bfd trifoliate foliage shows hair and trichomes, whereas below bfd 'O. subcuneata', for example, shows hair, files, and some trichomes. Most conspicuous in functional-group differences is that aliphatic side-chain branching is lower below than above bfd. It is suggested that aspects of Zimmermann's telomic theory may offer an explanation for the phenomenon.